Multicultural values in social studies learning using indirect teaching model in Junior High Schools - Anifah, Rifqi Nurul; Atmadja, Hamdan Tri; Juhadi, Juhadi (JESS (Journal of Educational Social Studies), 2022)
Multicultural values are an integrated value system including justice, diversity, freedom, and solidarity. SMP Negeri 2 Pemalang, SMP Pius Pemalang, and SMP Al-Irsyad Pemalang have students from various ethnicities, including Javanese, Chinese, and Arabic. This study aims to analyze the practice of multicultural teaching and learning activities in social studies subjects at junior high school by using the indirect teaching model, to analyze the role of social studies teachers in shaping the multicultural values in social studies learning, and to analyze the multicultural values students have through indirect teaching models. This writing was done qualitatively with a phenomenological approach. Data were collected through interviews, observation, and documentation study. The results show that not all social studies teachers understand the indirect teaching model before learning. Not all social studies materials could be delivered using the indirect teaching model. Apart from being an educator, teachers also play roles as an example of values, ethics, social and emotional aspects for students. The suggestion of this writing is to emphasize multicultural values to students to understand and apply them to social life, considering that Indonesia is currently experiencing a crisis of values, ethics, and morals.